Conflict and Integration in The Salafi-Wahabi Purification Movement in South Kalimantan - Muhammad Zainal Abidin; Yulia Hafizah (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2019)
This article intends to discuss the development of the Salafi-Wahabi movement in South Kalimantan in relation to conflict and integration. In South Kalimantan, the development of the Salafi-Wahabi movement was quite fast. Although less than two decades, this group's preaching has covered almost all regions in this province. The development of this group in recent years has become a topic of discussion among people in South Kalimantan, in both ways: pro and contra. This article employs a qualitative method that contains the study of literature and fieldwork. Fieldwork conducted in Banjar, South Kalimantan, to gather data related to the development of the Salafi-Wahabi movement and its implications to the changes community’s social order related to conflict and integration. The research shows that there are many issues of the Islamic purification movement that caused a strong response from the community that potentially prone to conflict. For example, are its teaching on Tawheed (monotheism) and accusation of many practices as bid’ah (heresy), which targeted respected local figures or groups like Guru Sekumpul in traditional circles. It becomes the main factor of the negative view of the Salaf-Wahabi group. However, there are some efforts made by Salafi-Wahabi to integrate their activities into the Banjar community.